Women's Need of Men in Danielle Steel's First Sight - Yusqi Qolbi (Journal of Feminism and Gender Studies, 2021)
This study aims to determine and analyze women's choices in the novel First Sight. This research focuses on the role of women who have high careers, and at the same time have feminine characteristics in themselves. Post-feminism theory is used to analyze elements related to women's choices in novels. This novel tells the story of a successful woman who tries to face and transcend her past in love as the background of the story. It shows the point of view of a successful woman in conquering her fears and getting her soul mate. Through this novel, Danielle Steel teaches us that women can have high careers and at the same time apply femininity to themselves. On the other hand, Steel also wants to answer women's concerns about women and mothers who have high careers in society.